Micro Interventions for Poverty Alleviation: The Philippine Case - Aniceto Jr. C. Orbeta; Maria Teresa Sanchez-Robielos (Philippine Institute for Development Studies (PIDS), 1996)
This paper provides a review of frameworks for analyzing poverty alleviation initiatives. The principles in these frameworks were used to guide the review of five micro-intervention programs/projects for poverty alleviation. The principles that can be useful in the design of future programs of this type are also presented. To provide a background to the review, the development performance of the country in the last 25 years is given together with a brief description of the poverty alleviation initiatives.
Keywords: 330; poverty measurement; Welfare Programs